Foreign Ownership and Skillbiased Technological Change - Michael Koch; Marcel Smolka (Center for Economic Studies and ifo Institute (CESifo), 2018)
We conduct an empirical investigation into the effects of foreign ownership on worker skills using firm-level data from Spain. To control for endogeneity bias due to selection into foreign ownership, we combine a difference-in-differences approach with a propensity score weighting estimator. Our results provide novel evidence that foreign-acquired firms actively raise the skills of their workforce in response to the acquisition by hiring high-skilled workers and providing worker training. To pin down the mechanism, we exploit unique information on whether firms use their foreign parent in exporting to foreign markets. Our results suggest a fundamental role for market access through the foreign parent in explaining skill upgrading in foreign-acquired firms. We reveal substantial productivity gains within foreign-acquired firms and we show that these gains derive from a concurrent effort to raise worker skills and adopt more advanced technology, suggesting a skill bias in technological innovations. We develop a simple theoretical model of foreign ownership featuring technology-skill complementarities in production that can rationalize our findings.
Keywords: D22; D24; F23; G34; 330; multinational enterprises; mergers and acquisitions; skill-biased technological change; worker training; productivity